Design and optimization of printed spiral coils for wireless passive sensors - Babak Noroozi; Bashir I. Morshed (IET Wireless Sensor Systems, 2021)
Abstract Monitoring physiological signals during regular life might provide many benefits including early detection of abnormalities and tracking the severities of diseases. A wireless connection between the passive sensor and the scanner eliminates the obtrusive wires, resolves battery‐related issues, and makes it easy‐to‐use. We have previously proposed a wireless resistive analogue passive sensor technique that operates with the help of inductive coupling. The variation of resistive physiological transducer (secondary side) leads to amplitude modulation on the scanner coil (primary side). The design of printed spiral coil (PSC) on printed circuit board, significantly affects the performance of the overall system in terms of sensitivity, the output voltage change as a reflection of the transducer change. To optimize the PSC's profile and maximize the sensitivity, we employ three methods: iterative, analytical, and genetic algorithm (GA). The GA optimized PSCs, as the best result, have been fabricated and the measurement showed a sensitivity of 0.72 mƱ which has 5% (8.8%) deviation from the simulation (theoretical) results. This method can be utilized to design a PSC pair in near‐field applications to transfer amplitude modulation with various sizes and fabrication constraints.